Characterization the influences of diodes to piezoelectric energy harvester. Issue 3 (3rd July 2018) - Yuan, Ming; Cao, Ziping; Luo, Jun
ABSTRACT: This study discloses the diode's influences on the piezoelectric energy harvesting performance. The piezoelectric-based energy harvesting system plays an important role in scavenging environment vibration energy into electrical energy, which can be utilized by low-power electronic devices. With respect to the interface circuit, a full-wave bridge circuit is usually needed to rectify the alternating current (AC) signal into a direct current (DC) signal. The full-wave bridge is composed of four diodes, whose characteristics may influence the harvested power significantly. Therefore, in this paper, the diodes' properties and influences on the energy harvesting performance are analyzed and presented via simulation and experimental studies. It is found the harvested energy has close relationship with the diode characteristics. For the high source impedance case, diode with low reverse leakage current is favorable. For the low source impedance case, diode with low forward voltage drop is favorable. The corresponding experimental study is carried out via a piezoelectric beam, which shows that the measured harvested power differences can almost be up to 800% for the same test structure.